2019
DOI: 10.1038/s42003-019-0629-6
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene nanoplastics disrupt glucose metabolism and cortisol levels with a possible link to behavioural changes in larval zebrafish

Abstract: Plastic nanoparticles originating from weathering plastic waste are emerging contaminants in aquatic environments, with unknown modes of action in aquatic organisms. Recent studies suggest that internalised nanoplastics may disrupt processes related to energy metabolism. Such disruption can be crucial for organisms during development and may ultimately lead to changes in behaviour. Here, we investigated the link between polystyrene nanoplastic (PSNP)-induced signalling events and behavioural changes. Larval ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(84 citation statements)
references
References 66 publications
6
76
2
Order By: Relevance
“…6 Differences with published data could also be attributed to the use of other ZF strains (e.g. AB/TL wild type as in van Pomeren et al, 48 Veneman et al, 10 Brun et al 7 or Sökmen et al 11 ), instead of wild type larvae as in our case. We decided to use wild type zebrafish (no strain) to approach the individual variability present in a natural population, in order to better emulate an environmental situation.…”
Section: In Vitro Toxicity Uptake and Accumulation Of Ps-nps In Zfl contrasting
confidence: 56%
See 2 more Smart Citations
“…6 Differences with published data could also be attributed to the use of other ZF strains (e.g. AB/TL wild type as in van Pomeren et al, 48 Veneman et al, 10 Brun et al 7 or Sökmen et al 11 ), instead of wild type larvae as in our case. We decided to use wild type zebrafish (no strain) to approach the individual variability present in a natural population, in order to better emulate an environmental situation.…”
Section: In Vitro Toxicity Uptake and Accumulation Of Ps-nps In Zfl contrasting
confidence: 56%
“…This pattern of accumulation has been previously reported although with some differences, likely due to the specific exposure time, dose, size and larvae age. For example, Brun et al observed accumulation of 25 nm PS-NPs (20 mg l −1 ) 7,8 in the intestine, exocrine pancreas and gall bladder after 48 h of exposure at 120 hpf (5 dpf). It is worth mentioning that there is a considerable variation in between studies, with PS-NPs being located in the intestine and neuromast, 7 in the heart region, 10 in the digestive track and eyes, 48 in the gut and gills region 49 and in the gastrointestinal tract, gallbladder, liver, pancreas, heart and brain.…”
Section: In Vitro Toxicity Uptake and Accumulation Of Ps-nps In Zfl mentioning
confidence: 99%
See 1 more Smart Citation
“…For the gut, pathological manifestations of MP/NP toxicity include documented changes in gut biomarkers related to epithelial barrier integrity, inflammation, and oxidative stress [83,86], as well as changes in gut microbiota [82,83,86]. In the case of liver, changes in metabolites, key metabolic enzymes, and oxidative stress-induced enzymes occur [49,74,79,81,85,87]. MPs/NPs could be internalized [88], and then cause detectable biomarker changes in blood cells [47,88,89].…”
Section: Toxicity Of Mps/nps In Fishesmentioning
confidence: 99%
“…Other applications of this line are listed in Fig. 4, which covers a considerable number of different physiological processes and underlies the value of the zebrafish model (Kwan et al 2016, Brun et al 2019, Mosser et al 2019, Palstra et al 2019, Sireeni et al 2020.…”
Section: Mutants Of Glucocorticoid Receptors In Zebrafishmentioning
confidence: 99%